2014
DOI: 10.1016/j.phytochem.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Crinine-type alkaloids from Hippeastrum aulicum and H. calyptratum

Abstract: An ongoing search for alkaloids in the Amaryllidaceae species using GC-MS resulted in the identification of two crinine-type alkaloids, aulicine (1) and 3-O-methyl-epimacowine, (2) from the indigenous Brazilian species Hippeastrum aulicum and Hippeastrum calyptratum, respectively. In addition, two alkaloids, 11-oxohaemanthamine (3) and 7-methoxy-O-methyllycorenine (4) were both isolated from H. aulicum. Furthermore, we provide here complete NMR spectroscopic data for the homolycorine analogues nerinine (5) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…This library has been regularly updated with alkaloids isolated and unequivocally identified via physical and spectroscopic methods. 18 NMR data for the known alkaloids described herein closely matched those reported elsewhere. [18][19][20][21][22][23][24][25][26] Mass spectra were deconvoluted using AMDIS 2.64 software (NIST) (WA, USA) and RIs recorded using a standard n-hydrocarbon calibration mixture (C9-C36).…”
Section: Identification Of Alkaloids By Cgc-mssupporting
confidence: 80%
See 3 more Smart Citations
“…This library has been regularly updated with alkaloids isolated and unequivocally identified via physical and spectroscopic methods. 18 NMR data for the known alkaloids described herein closely matched those reported elsewhere. [18][19][20][21][22][23][24][25][26] Mass spectra were deconvoluted using AMDIS 2.64 software (NIST) (WA, USA) and RIs recorded using a standard n-hydrocarbon calibration mixture (C9-C36).…”
Section: Identification Of Alkaloids By Cgc-mssupporting
confidence: 80%
“…Thirteen alkaloids are reported here for the first time in H. aulicum, although some chemical similarities with previous studies have also been found. 18,30 The H. aulicum studied here, from Biritiba-Mirim City (São Paulo, Brazil), displayed aulicine (15), haemanthamine (16), and lycorine (25) as the main compounds, as does H. aulicum from Cunha City (São Paulo, Brazil). 18 Both Brazilian cities are relatively close, which may explain the presence of the same major components.…”
Section: Alkaloid Comparisonmentioning
confidence: 71%
See 2 more Smart Citations
“…In total, 23 Amaryllidaceae alkaloids were isolated. Lycorine ( 1 ) was the main constituent of both Hippeastrum species, while haemanthamine ( 15 ) was abundant only in H. aulicum . The structures of the four new alkaloids were determined by spectroscopic investigation.…”
Section: Crinine Alkaloids Subgroupmentioning
confidence: 99%